Nitrite metabolism of several bacterial strains isolated from abattoir and swine wastewater after biogas treatment - Dinh, Thi Thu Hang; Nguyen, Thi Viet; Phan, Do Hung; Tran, Hoa Duan; Nguyen, Dang Giang Chau; Nguyen, Huu Dong (Hue University Journal of Science: Natural Science, 2022)
In nitrogen treatment with biological methods, nitrite metabolism is an intermediate process that facilitates other processes involving different bacteria strains. In this study, we isolated two nitrite-oxidising bacteria strains from abattoir wastewater and wastewater from biogas tanks of an industrial pig farm in Ha Tinh province. The bacteria strains grow, develop, and metabolise nitrite at pH 6–8 and 30–37 °C. The samples with the nitrite concentration up to 750 mg·L–1 were oxidised within four days of incubation, and the nitrite metabolism rate was proportional to the concentration of nitrite tested. Under severe conditions (salinity up to 3% NaCl, a low dissolved oxygen level of 0.1 mg·L–1), the two isolated bacterial strains exhibited their effective growth and nitrite metabolism capacity. The results enrich the database of nitrite-oxidising bacteria and are prospective in wastewater treatment.